2011
DOI: 10.1002/path.2849
|View full text |Cite
|
Sign up to set email alerts
|

Conditional β1‐integrin‐deficient mice display impaired pancreatic β cell function

Abstract: β1-Integrin, a critical regulator of β cell survival and function, has been shown to protect against cell death and promote insulin expression and secretion in rat and human islet cells in vitro. The aim of the present study was to examine whether the knockout of β1-integrin in collagen I-producing cells would have physiological and functional implications in pancreatic endocrine cells in vivo. Using adult mice with a conditional knockout of β1-integrin in collagen I-producing cells, the effects of β1-integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
64
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 75 publications
(95 reference statements)
7
64
1
Order By: Relevance
“…16 We found that mice with b1 integrin deficiency controlled by the collagen I promoter had a primary defect in PSCs and islets in the pancreas, which led to a significant decrease in ECM products in the exocrine compartment. b1 integrin-deficient mice displayed significantly decreased food intake with a loss of body weight, which was associated with reduced pancreatic amylase, carboxypeptidase A and regenerating islet-derived protein II expression.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…16 We found that mice with b1 integrin deficiency controlled by the collagen I promoter had a primary defect in PSCs and islets in the pancreas, which led to a significant decrease in ECM products in the exocrine compartment. b1 integrin-deficient mice displayed significantly decreased food intake with a loss of body weight, which was associated with reduced pancreatic amylase, carboxypeptidase A and regenerating islet-derived protein II expression.…”
mentioning
confidence: 83%
“…17 Progeny mice with positive genotype, as analyzed by polymerase chain reaction (PCR), 17 were induced by intraperitoneal injection of 1 mg tamoxifen (4-hydroxytamoxifen; Sigma, St Louis, MO, USA) per mouse per day for 5 days at 3 weeks of age. 16 Corn oil-injected Crepositive and tamoxifen-injected Cre-negative mouse groups were merged as controls (Ctrl) and experiments were carried out on male mice at 4 and 7 weeks post-injection. Deletion of b1 integrin was confirmed by quantitative RT-PCR, western blot and immunofluorescence as described previously.…”
Section: Materials and Methods Conditional B1 Integrin-deficient Micementioning
confidence: 99%
See 2 more Smart Citations
“…10 Integrins modulate multiple cellular processes in a variety of tissues. In the mouse pancreas, the conditional removal of β1 integrin leads to dysfunction of the endocrine 11 and exocrine 12 compartments. Removal of β1 integrin in developing pancreatic β cells leads to a massive reduction in insulin-positive cells and cell-cycle progression genes, suggesting that β cell expansion relies upon β1 integrin and ECM interactions.…”
mentioning
confidence: 99%